Echo‐planar spectroscopic imaging with dual‐readout alternated gradients (DRAG‐EPSI) at 7 T: Application for 2‐hydroxyglutarate imaging in glioma patients. Issue 4 (22nd August 2017) - An, Zhongxu; Tiwari, Vivek; Ganji, Sandeep K.; Baxter, Jeannie; Levy, Michael; Pinho, Marco C.; Pan, Edward; Maher, Elizabeth A.; Patel, Toral R.; Mickey, Bruce E.; Choi, Changho
Abstract : Purpose: To develop echo‐planar spectroscopic imaging (EPSI) with large spectral width and accomplish high‐resolution imaging of 2‐hydroxyglutarate (2HG) at 7 T. Methods: We designed a new EPSI readout scheme at 7 T. Data were recorded with dual‐readout alternated gradients and combined according to the gradient polarity. Following validation of its performance in phantoms, the new readout scheme, together with previously reported 2HG‐optimized magnetic resonance spectroscopy (point‐resolved spectroscopy echo time of 78 ms), was used for time‐efficient and high‐resolution imaging of 2HG and other metabolites in five glioma patients before treatment. Unsuppressed water, acquired with EPSI, was used as reference for multichannel combination, eddy‐current compensation, and metabolite quantification. Spectral fitting was conducted with the LCModel using in‐house calculated basis sets. Results: Using a readout gradient strength of 9.5 mT/m and slew rate of 90 mT/m/ms, dual‐readout alternated gradients EPSI permitted 1638‐Hz spectral width with 6 × 6 mm 2 in‐plane resolution at 7 T. Phantom data indicated that dual‐readout alternated gradients EPSI provides proper metabolite signals and induces much less frequency drifts than conventional EPSI. For a spatial resolution of 0.5 mL, 2HG was detected in tumors with precision (Cramer‐Rao lower bound < 10%). The 2HG was estimated to be 2.3 to 3.3 mM in tumors of three patients with biopsy‐proven isocitrate dehydrogenase (IDH) mutant gliomas. The 2HG was undetectable in an IDH wild‐type glioblastoma. For a radiographically suggested glioma, the estimated 2HG of 2.3 ± 0.2 mM (Cramer‐Rao lower bound < 10%) indicated that the lesion may be an IDH mutant glioma. Conclusions: The data indicated that the dual‐readout alternated gradients EPSI can provide reliable high‐resolution imaging of 2HG in glioma patients at 7 T in vivo. Magn Reson Med 79:1851–1861, 2018. © 2017 International Society for Magnetic Resonance in Medicine.